The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/sj.bdj.2016.262
|View full text |Cite
|
Sign up to set email alerts
|

Referrals to a facial pain service

Abstract: Aim :To determine who refers patients to a facial pain service, to assess the quality of the referral letters. MethodThe source of all referral letters to the service for 5 years were established. For one year the information provided in 94 referrals was assessed. Using a predetermined checklist of essential information the referral letters were compared to these set criteria. Results:The service received > 1000 referrals annually and on average GDPs referred 303 more patients per year than GMPs. 71% of all re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…This oversight can pose a high risk to patient safety, especially if the patient has been triaged into the wrong setting based on the information provided. A medical history including past and present medications helps prevent polypharmacy and encourages safer prescribing, in addition to assisting the specialist in creating a treatment plan without additional ‘time‐wasting’ correspondence with the referring practitioner. One study found that only 58% of referral letters gave an accurate list of medications and drug doses used by their patients.…”
Section: Discussionmentioning
confidence: 99%
“…This oversight can pose a high risk to patient safety, especially if the patient has been triaged into the wrong setting based on the information provided. A medical history including past and present medications helps prevent polypharmacy and encourages safer prescribing, in addition to assisting the specialist in creating a treatment plan without additional ‘time‐wasting’ correspondence with the referring practitioner. One study found that only 58% of referral letters gave an accurate list of medications and drug doses used by their patients.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Sufficient information is mandatory for allowing appropriate triage and for the assessment of clinical need and urgency. 2 , 18 Busy general practitioners prioritize chair time over administration, and there has to be benefits to both the referrer and the receiving specialist if a new referral system is to be successful. By raising the bar on submissions, the patients’ and society’s resources can be better allocated and utilized.…”
Section: Discussionmentioning
confidence: 99%
“…However, several published audits and studies have shown that the standards of oral surgery referrals are universally poor. 2 6 In this study, we performed a retrospective analysis of all routine oral surgery referrals received at two different oral surgery departments in Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed pain syndromes may also exist, where, rather than a binary distinction, pain may exist on a continuum of ‘more or less neuropathic’ [2, 3]. Due to a limited understanding of the pathophysiology of these processes, and the possibility of multiple OFP diagnoses occurring within the same patient, misdiagnosis and inappropriate referral of these patients is common, particularly for non-specialist clinicians [4, 5]. The management of musculoskeletal compared to neuropathic origin varies.…”
Section: Introductionmentioning
confidence: 99%
“…Testing the PD-Q across a broad range of facial pain diagnoses is required to determine whether this tool would have utility as a screening tool for neuropathic pain in OFP. Our centre receives a heterogeneous group of patients with OFP [5], providing an opportunity to assess the PD-Q in a secondary care setting. The aim of this study was to determine the utility of the PD-Q to detect neuropathic pain in a hospital-based cohort of patients with OFP.…”
Section: Introductionmentioning
confidence: 99%